Handbook of Health Behavior Research III
XXVIII, 456 p.
Keywords: Volume 3 relates the demography of health behavior to developmental and diversity issues. Unique discussions of the health behaviors of gay males, lesbians, persons with HIV, and caregivers themselves are included. Each volume features extensive supplementary and integrative matrial prepared by the editor, the detailed index to the entire four-volume set, and a glossary of health behavior terminology.